Instruction, Assessment, and Intervention Practices in DMDL: A Multiple Case Study - May Anne Batain (Qubahan Academic Journal)
The study aimed to determine the teaching practices of senior high school faculty in an integrated school in Calamba City, Laguna Philippines, offering a digital modular distance learning modality. Specifically, it sought to determine how teachers facilitate instruction, assess learning, and remediate least learned competencies.